PERAN ORANG TUA DALAM MENDUKUNG KEGIATAN PEMBELAJARAN BACA TULIS AL-QUR’AN ANAK USIA 5-6 TAHUN DI RA AN-NURIYAH CIPONDOH MAKMUR - Hafifah Mawaddah; Siti Istiqomah (Fakultas Tarbiyah IIQ Jakarta, 2023)
This writing is motivated by the fact that there are still many children who are not aware of the importance of learning to read and write the Qur'an. This is seen by the author from the results of observations at RA An-Nuriyah Cipondoh Makmur. Therefore, it is necessary to have support from parents in supporting reading and writing activities of the Qur'an in children. This writing aims to determine the role of parents in supporting reading and writing activities of the Qur'an for children aged 5-6 years at RA An-Nuriyah Cipondoh Makmur. This type of research is qualitative research with descriptive analysis research methods, and data collection techniques used are; observation, interviews, and documentation, as for the data analysis techniques, namely using data reduction, data presentation, and drawing conclusions. The results of the writing show that the role of parents is very important in supporting reading and writing activities of the Qur'an in children. Among the roles of parents are as role models and role models, as mentors and coaches, as supervisors and controllers, and as facilitators.